THE ROLE OF DIGITAL TECHNOLOGY IN SUPPORTING DISASTER EMERGENCY RESPONSE: LITERATURE REVIEW (Proceedings OPTIMAL, 2025)
Background: The increasing frequency and complexity of global disasters require health care systems to respond quickly, appropriately, and in a coordinated manner. Digital technology is a strategic solution to strengthen emergency response capacity, especially in the triage process, communication, and training of health workers.Objective: This study aims to systematically review the use of digital technology in the context of disaster emergency response, with a focus on nursing and pre-hospital services. The study evaluates the types of technology used, their impact on service effectiveness, and implementation challenges in the field.Method: A systematic review method was used with reference to the PRISMA guidelines. Searches were conducted on the PubMed, Scopus, and ScienceDirect databases using a combination of keywords related to disasters, digital technology, and health workers. A total of 707 articles were obtained, filtered based on inclusion and exclusion criteria, leaving 12 articles for narrative analysis.Results: Four main themes were found: (1) mobile applications and digital triage systems, (2) utilization of telemedicine and telenursing, (3) integration of artificial intelligence and digital sensors, and (4) innovation in nursing training and documentation. This technology has been shown to improve the speed of patient classification, access to remote medical services, and health worker preparedness. However, limited infrastructure, digital literacy, and ethical aspects are significant challenges.Conclusion: Digital technology has great potential to improve the quality and efficiency of disaster response. Policies that support inclusive technology integration, as well as ongoing training for health workers are needed to ensure successful implementation across disaster contexts.